Research on Water Flow Control Strategy for PEM Electrolyzer Considering the Anode Bubble Effect - Liheng An; Yizhi Tian; Haikun Zhao (Energies)
At higher current densities, the bubble effect in the anode flow field of the PEM electrolyzer (PEM EL) worsens mass transfer losses and energy consumption. This study employs a moderate increase in the water flow rate to remove accumulated bubbles under fluctuating electrical input, thereby improving PEM EL system efficiency. An enhanced PEM EL equivalent circuit model incorporating bubble over-potential based on the oxygen volume fraction is developed. Considering the energy consumption of auxiliary equipment and the reduction in losses from mitigating the bubble effect, a numerical simulation evaluates the impact of flow rate variations on overall electrolysis energy consumption, leading to a comprehensive energy consumption model for the PEM EL system, incorporating electrical, chemical, and thermal energy conversions. The control objective is to maximize system efficiency by optimizing the water flow rate, with a performance-preset-based controller implemented in MATLAB/Simulink. The simulation results show that the controller can accurately track the target flow rate, and the dynamic regulation time improved by 1.5 s compared to the traditional performance constraint function, better matching the rate of change in electrical energy. Under the water flow control mode, hydrogen production increased by 6.6 L within 130 s of the simulation, available energy increased by 8.32 × 106 J, and the efficiency of the PEM EL system improved by 2.79%.